Service Learning in History and Cultural Learning in Red Square Area, Melaka, Malaysia - Satriadi Satriadi; Agus Purnomo Sidi; Endarwita Endarwita; Ai Salsa Agustina; Dinda Tiara Kasih; Herlyn Herlyn (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
The Rumah Merah Melaka heritage tourist area has an important historical value, but the information received by tourists about its historical value is still limited, so the understanding gained by tourists is not optimal. This community service activity aims to increase the historical literacy of tourists and the involvement of local business actors in cultural preservation through the provision of educational media and mentoring with participatory methods oriented to the needs of the target community. The implementation stages include observation to identify the information needs of tourists and the role of local communities, the preparation of historical educational media according to the socio-cultural context, the implementation of direct education to tourists, and the assistance of local business actors as independent distributors of cultural information. The results show an increase in tourists' interest in the historical information provided, changes in tourist behavior in paying attention to cultural values, and the active participation of local business actors in the delivery of historical information. This program is expected to contribute to improving the quality of tourism experiences, strengthening the capacity of local communities, and supporting the sustainability of heritage preservation through collaboration between the community, local business actors, and visitors.